Involvement of Recombination Genes in Growth and Viability of Escherichia coli K-12 - Capaldo-Kimball, Florence (1971)
We have studied the growth properties of 17 isogenic strains of Escherichia coli K-12 differing only in the recA, recB, recC, and sbcA alleles. We have observed the following. (i) All recombination deficient strains have decreased growth rates and decreased viabilities compared with recombination proficient strains. The large populations of nonviable cells in Rec(−) cultures may arise by spontaneous lethal sectoring (9). (ii) A recA mutant strain which is entirely recombination deficient and which shows high ultraviolet sensitivity and “reckless” deoxyribonucleic acid (DNA) breakdown has approximately the same growth rate and twice the viability as recB and recC mutant strains which have residual recombination proficiency, moderate ultraviolet sensitivity, and “cautious” DNA breakdown. (iii) Indirectly suppressed (sbcA(−)) recombination proficient (Rec(+)) revertants of recB and recC mutant strains have approximately normal growth rates and are three times as viable as their Rec(−) ancestors (but not as viable as rec(+) cells). We suggest the following hypothesis to account for the low viability of Rec(−)E. coli. Single-strand breaks in the DNA duplex, necessary for normal bacterial growth, may be repaired in a Rec(+) cell. Failure of Rec(−) cells to repair this normal DNA damage may lead to the observed loss of viability.